IDDAH BAGI PEREMPUAN PASCA PERCERAIAN DALAM AL-QUR’AN(Kandungan Surah Al-Baqarah Ayat 228 Tentang Masa Iddah Bagi Perempuan) - Tajul Iflah; Raihan Putri (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAI ALMUSLIM, 2024)
This research was conducted to find out what the legal status of women's iddah is after divorce and what is the interpretation of the Al-Qur'an Surah Al-Baqarah Verse 228 regarding women's iddah period. This research uses a qualitative descriptive approach which is carried out to solve problems that relies on a critical and in-depth review of relevant library materials. The type of research used in this research is library research. The research results show that the legal status of women's iddah after divorce is that women who have been divorced by their husbands are obliged to wait for their iddah period. The iddah period for women who are divorced by their husband is three quru' or three holy times. The interpretation of the Al-Qur'an Surah Al-Baqarah verse 228 regarding the iddah period for women who are divorced by their husband is three times quru' or three times holy. Three times quru' is interpreted as three holy times after menstruation for women. Imam Syafi'i believes that quru' is holy, not menstruation. The final limit when it is halal for a husband to refer to his wife is at the end of the third holy period, when she has entered her third menstruation, the husband can no longer refer to his wife and she is halal for other men.